(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Cerebrospinal fluid (CSF) leakage is a substantial complication that results from spinal dysraphism surgery, which contributes to prolonged hospital stays and increased morbidity rate. Objectives: This investigation was carried out to ascertain the frequency of immediate postoperative CSF leakage, identify risk factors that are associated with these leaks and assess the clinical outcomes in patients who are undergoing spinal dysraphism surgery. Methods: From January to December 2023, 40 patients who underwent surgery for spinal dysraphism were included in this cross-sectional study. The analysis encompassed postoperative outcomes, clinical characteristics, surgical details and patient demographics. Focusing on factors such as intraoperative complications, surgical complexity and tethered cord syndrome, statistical comparisons were conducted between patients with and without CSF leakage. Results: Six patients (15%) experienced CSF leaks, with statistically significant association observed in those with tethered cord syndrome (66.7 vs. 23.5%, p<0.05) and surgeries lasting more than 120 minutes (66.7 vs. 23.5%, p<0.05). Reoperation rates were considerably higher (33.3 vs. 2.9%, p<0.01) and patients with CSF leaks had significantly longer hospital stays (12.5 ± 4.1 days vs. 7.4 ± 2.8 days, p<0.01). The group that experienced CSF leaks experienced a significantly higher incidence of infections, with a meningitis incidence of 33.3% (p<0.05). Patients with CSF leaks required substantially more lumbar drainage and returned to the operating room (p<0.05). Conclusion: CSF leakage is a comparatively frequent complication of spinal dysraphism surgery, particularly in patients with tethered cord syndrome and prolonged surgical procedures. The risk of infection, reoperation and morbidity rate is substantially elevated by the presence of a CSF leak.